Longitudinal detection of somatic mutations in the saliva of head and neck squamous cell carcinoma–affected patients: a pilot study - Dal Secco, Chiara; Tel, Alessandro; Allegri, Lorenzo; Baldan, Federica; Curcio, Francesco; Sembronio, Salvatore; Faletra, Flavio; Robiony, Massimo; Damante, Giuseppe; Mio, Catia (Frontiers in Oncology, 2024)
IntroductionLiquid biopsy is gaining momentum for diagnosis and surveillance of cancer patients. Indeed, head and neck squamous cell carcinoma (HNSCC) is burdened with poor prognosis and high recurrence rates after treatment. It is therefore crucial to be able to detect minimal residual disease early after radical treatment or relapse, so surgery can be performed when the disease is still resectable. In this scenario, aim of this study is to create a liquid biopsy-based pipeline able to detect somatic tumor mutations in a cohort of HNSCC-affected patients undergoing follow-up after surgical intervention.MethodsOur cohort included 17 patients diagnosed with HNSCC over 4 years. The first saliva sample was collected before surgery while the rest were collected during the subsequent visits, according to the follow-up schedule. Salivary DNA (sDNA) was extracted, and a 52-gene next generation sequencing (NGS)-based panel was used for somatic variants detection.Results41.2% of samples collected before surgery bore a deleterious variant (n=7/17). Overall, 29.2% of samples harbored at least a pathogenic variant (n=21/72). The most frequently mutated genes were TP53 (80%), FBXW7 (8%), PDGFRA (4%) and PTEN (4%). Finally, three patients experienced a loco-regional relapse by clinical evaluations, anticipated in 67% of cases by the molecular one (n=2/3).DiscussionOur data indicate that sDNA could aid in the monitoring of patients’ follow-up as low-frequency somatic mutations could be assessed from the saliva of HNSCC patients. Prospectively, these results suggest that salivary-based liquid biopsy might pave the way for personalized molecular therapies based on mutational data.